The geopolitics of free trade: Impact of the trade war between China and the United States on the renegotiation of the North American Free Trade Agreement (NAFTA) - Medina Rivas Plata, Anthony (2022)
This paper seeks to analyze the geopolitical causes of the renegotiation of the North American Free Trade Agreement (TLCAN / NAFTA) until the generation of the new United States Mexico Canada Agreement (T-MEC / USMCA). We consider that the advance of China within the supply chains that enter the geographic area of North America, the existing asymmetries in the productive structures of Mexico and its two northern partners, as well as the new protectionist tendencies in the United States generated the conditions for the renegotiation of the agreement, which creates incentives to prioritize the production of industrial material within the USMCA space against competition from Chinese products. We will do a discussion about the favorable and unfavorable aspects for the implementation of the new agreement and the new perspectives on its possible impact on the automotive industry, which was one of the central aspects that led to its renegotiation.